REGULARITIES OF EMERGENCE AND DEVELOPMENT OF NEW SPECIES AND FORMS OF THE FORENSIC SCIENCE - N. Neretina (Теория и практика судебной экспертизы)
The regularities of the emergence and development of new species аnd forms of the forensic science are shown.